2016
DOI: 10.4238/gmr.15038342
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the association between XRCC1 gene polymorphisms and susceptibility to gastric cancer

Abstract: ABSTRACT. We carried out a hospital-based case-control study to investigate the role of XRCC1 gene Arg399Gln, Arg280His, and Arg194Trp polymorphisms in susceptibility to gastric cancer. A total of 214 gastric cancer patients and 247 control subjects were recruited between March 2013 and March 2015, and polymorphism genotype frequencies were determined by polymerase chain reactionrestriction fragment length polymorphism. Using the chi-square test, we detected statistically significant differences in age (chi-sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…XRCC1 plays a key role in mediating the repair of single-stranded DNA breaks as part of the BER pathway, with SNPs in this gene having the potential to alter or compromise protein functionality (3,19,24,25). Mutations in XRCC1 have been linked with many different cancer types, including hepatocellular carcinoma, thyroid carcinoma, nasopharyngeal carcinoma, and lung, bladder, gastric, and cervical cancers (16,(26)(27)(28)(29)(30)(31)(32). Previous studies have focused largely on three different XRCC1 polymorphisms when assessing their relationship with esophageal cancer risk, including Arg280His, Arg194Trp, and Arg399Gln (3,11,13,33).…”
Section: Discussionmentioning
confidence: 99%
“…XRCC1 plays a key role in mediating the repair of single-stranded DNA breaks as part of the BER pathway, with SNPs in this gene having the potential to alter or compromise protein functionality (3,19,24,25). Mutations in XRCC1 have been linked with many different cancer types, including hepatocellular carcinoma, thyroid carcinoma, nasopharyngeal carcinoma, and lung, bladder, gastric, and cervical cancers (16,(26)(27)(28)(29)(30)(31)(32). Previous studies have focused largely on three different XRCC1 polymorphisms when assessing their relationship with esophageal cancer risk, including Arg280His, Arg194Trp, and Arg399Gln (3,11,13,33).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis found the G allele is one of the risk factors in developing of Glioma in Asians [ 84 ]. Another meta-analysis carried out on a Chinese population found XRCC1 Arg399Gln polymorphism is not associated with BC (at the 5% level) but indicated a borderline association [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated an association between XRCC1 genetic polymorphisms and a variety of cancers such as gastric (Chen et al, 2016), lung (Cătană et al, 2015), thyroid (Wang et al, 2015) and breast cancer (Bu et al, 2014). This study aimed to investigate c.1517G>C SNP of XRCC1 gene as HCC risk factor in Egyptian population.…”
Section: Introductionmentioning
confidence: 99%